Assessing the Proportion of Conformance of a Process from a Bayesian Perspective. (29th November 2013) - Perakis, Michael; Xekalaki, Evdokia
Abstract : A Bayesian technique for assessing the posterior probability that the proportion of conformance of a normally distributed process exceeds a particular value is suggested. Both exact and approximate formulae for the assessment of this probability are derived. Copyright © 2013 John Wiley & Sons, Ltd.